Impact of wildfire return interval on the ectomycorrhizal resistant propagules communities of a Mediterranean open forest. - Buscardo, Erika; Rodríguez-Echeverría, Susana; Martín, María P.; De Angelis, Paolo; Pereira, João Santos; Freitas, Helena (Fungal biology, 2010)
Ectomycorrhizal (ECM) fungi, in particular their spores and other resistant propagules, play an important role in secondary succession processes that facilitate regeneration after disturbance events. In this study, the effects of high and low wildfire frequencies (respectively short and long fire return intervals) on the resistant propagules communities (RPCs) of a Mediterranean open pine forest were compared. Soil samples were collected in four mountain sites with different fire return intervals and used to test ectomycorrhiza development in two hosts, Pinus pinaster and Quercus suber. RPCs were characterized by direct sequencing of fungal internal transcribed spacer (ITS) regions from individual ECM root tips. Eighteen ECM species were detected in the bioassay. The most frequently found fungi were Cenococcum geophilum, Inocybe jacobi, Thelephora terrestris, Tomentella ellisii on both hosts and Rhizopogon luteolus and R. roseolus on maritime pine. A short fire return interval reduced the species richness of the ECM community found on Q. suber, promoted species like R. roseolus and reduced the abundance of other species (e.g. R. luteolus). The abundance of I. jacobi was positively affected by long fire return interval, but decreased significantly with recurrent fires. These results indicate that changes in fire frequency can alter the structure, composition and diversity of ECM communities, which could compromise the resilience of the ecosystem in highly disturbed areas.
The following values have no corresponding Zotero field: accession-num: 20943174
Keywords: Ectomycorrhizal resistant propagules community; Fire return interval; Mediterranean ecosystem; Pinus pinaster (maritime pine); Quercus suber (cork oak); succession

Relevance of genetics for conservation policies: the case of Minorcan cork oaks - Lorenzo, Zaida; Burgarella, Concetta; de Heredia, Unai López; Lumaret, Roselyne; Petit, Rémy J; Soto, Álvaro; Gil, Luis; Soto, Álvaro; Gil, Luis (Annals of Botany, 2009)
Background and Aims Marginal populations of widely distributed species can be of high conservation interest when they hold a significant or unique portion of the genetic diversity of the species. However, such genetic information is frequently lacking. Here the relevance of genetic surveys to develop efficient conservation strategies for such populations is illustrated using cork oak (Quercus suber) from Minorca (Balearic Islands, Spain) as a case study. Cork oak is highly endangered on the island, where no more than 67 individuals live in small, isolated stands in siliceous sites. As a consequence, it was recently granted protected status.Methods Two Bayesian clustering approaches were used to analyse the genetic structure of the Minorcan population, on the basis of nuclear microsatellite data. The different groups within the island were also compared with additional island and continental populations surrounding Minorca.Key Results Very high genetic diversity was found, with values comparable with those observed in continental parts of the species' range. Furthermore, the Minorcan oak stands were highly differentiated from one another and were genetically related to different continental populations of France and Spain.Conclusions The high levels of genetic diversity and inter-stands differentiation make Minorcan cork oak eligible for specific conservation efforts. The relationship of Minorcan stands to different continental populations in France and Spain probably reflects multiple colonization events. However, discrepancy between chloroplast DNA- and nuclear DNA-based groups does not support a simple scenario of recent introduction. Gene exchanges between neighbouring cork oak stands and with holm oak have created specific and exceptional genetic combinations. They also constitute a wide range of potential genetic resources for research on adaptation to new environmental conditions. Conservation guidelines that take into account these findings are provided.
From Duplicate 2 (Relevance of genetics for conservation policies: the case of Minorcan cork oaks - Lorenzo, Zaida; Burgarella, Concetta; de Heredia, Unai López; Lumaret, Roselyne; Petit, Rémy J; Soto, Álvaro; Gil, Luis)
Keywords: Balearic Islands; cluster analysis; conservation guidelines; Conservation of Natural Resources; Genetic Variation; Geography; marginal populations; Minorca; Nuclear microsatellites; Population Dynamics; Q. ilex (holm oak); Quercus; Quercus suber (cork oak); Quercus: genetics; Soil; Spain; western Mediterranean

Relevance of genetics for conservation policies: the case of Minorcan cork oaks - Lorenzo, Zaida; Burgarella, Concetta; de Heredia, Unai López; Lumaret, Roselyne; Petit, Rémy J.; Soto, Álvaro; Gil, Luis; Soto, Álvaro; Gil, Luis (Annals of Botany, 2009)
Background and Aims Marginal populations of widely distributed species can be of high conservation interest when they hold a significant or unique portion of the genetic diversity of the species. However, such genetic information is frequently lacking. Here the relevance of genetic surveys to develop efficient conservation strategies for such populations is illustrated using cork oak (Quercus suber) from Minorca (Balearic Islands, Spain) as a case study. Cork oak is highly endangered on the island, where no more than 67 individuals live in small, isolated stands in siliceous sites. As a consequence, it was recently granted protected status.Methods Two Bayesian clustering approaches were used to analyse the genetic structure of the Minorcan population, on the basis of nuclear microsatellite data. The different groups within the island were also compared with additional island and continental populations surrounding Minorca.Key Results Very high genetic diversity was found, with values comparable with those observed in continental parts of the species' range. Furthermore, the Minorcan oak stands were highly differentiated from one another and were genetically related to different continental populations of France and Spain.Conclusions The high levels of genetic diversity and inter-stands differentiation make Minorcan cork oak eligible for specific conservation efforts. The relationship of Minorcan stands to different continental populations in France and Spain probably reflects multiple colonization events. However, discrepancy between chloroplast DNA- and nuclear DNA-based groups does not support a simple scenario of recent introduction. Gene exchanges between neighbouring cork oak stands and with holm oak have created specific and exceptional genetic combinations. They also constitute a wide range of potential genetic resources for research on adaptation to new environmental conditions. Conservation guidelines that take into account these findings are provided.
From Duplicate 2 (Relevance of genetics for conservation policies: the case of Minorcan cork oaks - Lorenzo, Zaida; Burgarella, Concetta; de Heredia, Unai López; Lumaret, Roselyne; Petit, Rémy J; Soto, Álvaro; Gil, Luis)From Duplicate 2 (Relevance of genetics for conservation policies: the case of Minorcan cork oaks - Lorenzo, Zaida; Burgarella, Concetta; de Heredia, Unai López; Lumaret, Roselyne; Petit, Rémy J; Soto, Álvaro; Gil, Luis)The following values have no corresponding Zotero field: accession-num: 19671575
Keywords: Balearic Islands; cluster analysis; conservation guidelines; Conservation of Natural Resources; Genetic Variation; Geography; marginal populations; Minorca; Nuclear microsatellites; Population Dynamics; Q. ilex (holm oak); Quercus; Quercus suber (cork oak); Quercus: genetics; Soil; Spain; western Mediterranean

Competitive strategies for water availability in two Mediterranean Quercus species - Nardini, A.; Gullo, M. A. Lo; Salleo, S. (Plant, Cell & Environment, 1999)
Competition for water availability was studied in a mixed natural stand of Quercus suber L. and Quercus cerris L. growing in Sicily by measuring diurnal changes of leaf conductance to water vapour (gL), water potential (ΨL) and relative water content (RWC) in April, July and October 1997 as well as the seasonal changes in root hydraulic conductance per unit leaf surface area (KRL). Quercus cerris behaved as a drought-tolerant species, with strong reductions of KRL, ΨL, and RWC in the summer. By contrast, Q. suber appeared to withstand summer drought by an avoidance strategy based on reducing gL, maintaining ΨL and RWC high and KRL at the same level as that measured in the spring. A ‘conductance ratio’ (CR) was calculated in terms of the ratio of gL to KRL. Seasonal changes of this ratio contrasted in the two species, thus suggesting that Q. suber and Q. cerris did not really compete for available water. In the summer, when Q. suber was extracting water from the soil to maintain high leaf hydration, Q. cerris had restricted water absorption, thus suffering drought but tolerating its effects. The possibility that cohabitation of drought-tolerant with drought-avoiding species can be generalized is also discussed.
Keywords: leaf conductance; leaf water status; Quercus cerris (Turkey Oak); Quercus suber (cork oak); root hydraulic conductance.

Competitive strategies for water availability in two Mediterranean Quercus species - Nardini, A; Gullo, M A Lo; Salleo, S (Plant, Cell & Environment, 1999)
Competition for water availability was studied in a mixed natural stand of Quercus suber L. and Quercus cerris L. growing in Sicily by measuring diurnal changes of leaf conductance to water vapour (gL), water potential (ΨL) and relative water content (RWC) in April, July and October 1997 as well as the seasonal changes in root hydraulic conductance per unit leaf surface area (KRL). Quercus cerris behaved as a drought-tolerant species, with strong reductions of KRL, ΨL, and RWC in the summer. By contrast, Q. suber appeared to withstand summer drought by an avoidance strategy based on reducing gL, maintaining ΨL and RWC high and KRL at the same level as that measured in the spring. A ‘conductance ratio’ (CR) was calculated in terms of the ratio of gL to KRL. Seasonal changes of this ratio contrasted in the two species, thus suggesting that Q. suber and Q. cerris did not really compete for available water. In the summer, when Q. suber was extracting water from the soil to maintain high leaf hydration, Q. cerris had restricted water absorption, thus suffering drought but tolerating its effects. The possibility that cohabitation of drought-tolerant with drought-avoiding species can be generalized is also discussed.
Keywords: leaf conductance; leaf water status; Quercus cerris (Turkey Oak); Quercus suber (cork oak); root hydraulic conductance.